2019
DOI: 10.20517/2394-4722.2018.88
|View full text |Cite
|
Sign up to set email alerts
|

Can microcalcifications' characteristics predict the risk of breast cancer metastasis to bone?

Abstract: Aim:To correlate the microcalcifications' characteristics, such as morphology and elemental compositions, with the occurrence of bone metastatic lesions at 5 years from diagnosis. Methods:In this retrospective study, we enrolled 70 patients from which we collected one breast biopsy each. From each biopsy, paraffin serial sections were obtained to perform histological classifications, immunohistochemical analyses and Energy Dispersive X-ray evaluation.Results: Microcalcifications analysis showed a significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It was found that pathological nHAP induced bone metastasis through OLC activation. [ 202 ] The expression of OLC‐related biomarkers such as receptor activator of nuclear factor kappa‐Β ligand (RANKL) and runt‐related transcription factor 2 (RUNX2) is associated with bone metastasis of tumor. For example, vimentin‐RUNX2‐RANKL positive patients are more likely to develop bone metastasis within 5 years after diagnosis.…”
Section: The Role Of Nhap In Tumor Metastasis—a Double‐edged Swordmentioning
confidence: 99%
“…It was found that pathological nHAP induced bone metastasis through OLC activation. [ 202 ] The expression of OLC‐related biomarkers such as receptor activator of nuclear factor kappa‐Β ligand (RANKL) and runt‐related transcription factor 2 (RUNX2) is associated with bone metastasis of tumor. For example, vimentin‐RUNX2‐RANKL positive patients are more likely to develop bone metastasis within 5 years after diagnosis.…”
Section: The Role Of Nhap In Tumor Metastasis—a Double‐edged Swordmentioning
confidence: 99%